Physiological performance of soybean seeds in the accelerated aging test and their germination after several waiting periods - Rodrigues,Mayara (2022)
Abstract: The accelerated aging test is widely used to evaluate the vigor of soybean seeds. Currently, the methodology recommended in the literature is to set up the germination test at most one hour after the seed aging process, which makes it difficult to set up and evaluate a large number of samples. The aim of this study was to assess the effect of delay in setting up the germination test after the process of accelerated aging of soybean seeds, specifically its effect on seed physiological performance. We tested three seed lots of the soybean cultivars BRS 397, BRS 399 RR, BRS 1007 IPRO, BRS 1010 IPRO, and BRS 388, all within the standards required for commercialization. The seed lots were physiologically characterized by evaluation of moisture content, germination, seedling vigor classification, tetrazolium test (viability and vigor) and accelerated aging test. The treatments consisted of hours (0, 1, 2, 3, 4, 5, 6, 7, and 8) of delay in setting up the germination test after accelerated aging. A delay of up to eight hours in setting up the germination test after the accelerated aging process of soybean seeds has no direct relationship with the result of assessment of the physiological performance of the seed lot.